Bahan Ajar Pembelajaran Menulis Teks Laporan Hasil Observasi - Amay Unggu Anggria; Dawud Dawud; Imam Agus Basuki (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2018)
Abstract: This development research aims (1) to produce instructional material to write a text of report on observations that are feasible in terms of content by covering aspects of identifying and constructing the text of the observation report and (2) testing the effectiveness of teaching materials to write the text of the observation report. The research-development method was adapted from Borg and Gall's model. Product feasibility test results are include 82% content, 82% systematic presentation, 83% language feasibility, and 85% display feasibility. The results of the test of the effectiveness of the product are known p = 0.000 (p <0.01). Thus the product has a significant influence on the learning result of  report on observation text writing.Abstrak: Penelitian pengembangan ini bertujuan (1) menghasilkan bahan ajar menulis teks laporan hasil observasi yang layak dari segi isi, meliputi aspek mengidentifikasi dan mengonstruksi teks laporan hasil observasi dan (2) menguji keefektifan bahan ajar menulis teks laporan hasil observasi. Metode penelitian pengembangan diadaptasi dari model Borg dan Gall. Hasil uji kelayakan produk meliputi kelayakan isi 82%, kelayakan sistematika penyajian 82%, kelayakan bahasa 83%, dan kelayakan tampilan 85%. Hasil uji keefektifan produk diketahui nilai p = 0.000 (p < 0.01). Dengan demikian, produk memiliki pengaruh yang signifikan terhadap kemampuan menulis teks laporan hasil observasi.